12-NEIGHBOUR PACKINGS OF UNIT BALLS IN E-3 - Böröczky Károly (ACTA MATHEMATICA HUNGARICA, 2015)
We prove that any 12-neighbour packing of unit balls in is composed of parallel layers of the same hexagonal structure as the layers in the densest lattice packing.